Discovering class-specific visual patterns for visual recognition - Weng, Chaoqun (2017)
Similar to frequent patterns in data mining, visual pattern refers to a recurring composition of visual contents in images or videos, such as repetitive texture regions, common objects among images, or similar actions among videos. Such visual patterns capture the recurrence nature of visual data and can represent the essence of the visual data. Finding such visual patterns is critical to image and video data analysis.